Public-Private Employment Choice, Wage Differentials and Gender in Turkey - Aysit Tansel (Yale University, Economic Growth Center, 1999)
There is no evidence on the extent of public versus private wage differentials in Turkey. The main objective of this paper is to examine the factors which explain the employment choice and the wage differentials in the public administration, state owned enterprises and the formal private wage sector in Turkey. Selectivity corrected wage equations are estimated for each sector for men and women separately. Oaxaca decomposition of the wage differentials between sectors for men and women are carried out. For this purpose, results of the 1994 Household Expenditure Survey conducted by the State Institute of Statistics are used. The results indicate that when controlled for observed characteristics and sample selection, for men, public administration wages are at parity or lower than private sector wages in particular at the university level. State Economic Enterprise wages for men are higher than private sector wages except at the university level. Opposite results are obtained for women: their wages are at par or higher in public administration than in the private sector. Further, while men's and women's wages are at parity in public administration, there is a large gender wage- gap in the private sector. Lower private returns to schooling are found in public than in the private sector.
Keywords: J31; J45; J16; 330; Public-Private Wages; gender; Turkey; Lohnstruktur; Privatwirtschaft; Öffentliche Verwaltung; Öffentliches Unternehmen; Lohnstruktur; Geschlecht; Türkei